Transcriptomic suppression of immune and ECM stability in skeletal muscle of patients with chronic kidney disease - Luke A. Baker; Nicholas Eastley; Robert U. Ashford; Matthew Denniff; Matthew Graham-Brown; Emma L. Watson (PLoS ONE, 2026)
Background Chronic kidney disease (CKD) is a growing public health emergency with a global prevalence of approximately 14%. Sarcopenia is a common complication of CKD contributing to functional decline and poor outcomes. However, the molecular mechanisms driving muscle wasting in CKD remain incompletely understood. This study aimed to characterise the transcriptomic profile in individuals with CKD compared to healthy control counterparts, to identify key pathways implicated in muscle dysfunction. Methods Vastus lateralis muscle biopsy samples were obtained from n = 10 people with CKD and n = 9 healthy controls matched for age, sex, ethnicity and physical activity. Bulk RNA sequencing was performed on all samples. Differential gene expression was assessed using DESeq2 and pathway enrichments analyses were conducted using Gene Ontology (GO) and KEGG databases. Results Seventy-six genes were differentially expressed in CKD muscle (FDR < 0.05, |log₂FC| ≥ 1), with 62 downregulated and 14 upregulated. he most consistent signature was suppression of immune-related and extracellular matrix transcripts, including CD163, C1QC, MPEG1, CXCL14, ITIH5, PODN, and CCDC80, suggesting attenuated immune surveillance and reduced ECM stability. In contrast, haemoglobin subunit genes (HBB, HBA1) were upregulated, potentially reflecting compensatory adaptation in oxygen transport. Several genes linked to regenerative processes (e.g., MEGF10, SOX4) were differentially expressed, but canonical myogenic and catabolic regulators remained unchanged, indicating that CKD muscle exists in a transcriptionally blunted state rather than one of overt inflammation or proteolysis. Conclusions CKD skeletal muscle is characterised by suppression of immune and ECM regulatory programmes, with limited evidence for activation of classical inflammatory or degradative pathways. This distinct transcriptional profile suggests an immunologically and structurally quiescent state that may impair repair capacity and contribute to progressive sarcopenia. These findings refine current understanding of CKD-associated muscle dysfunction and highlight potential targets for mechanistic and therapeutic exploration.